Pemberdayaan Masyarakat Desa Margahayu dalam Pencegahan Kejahatan Siber Melalui Literasi Digital - Hendarman Lubis; Krisna Darmawan; Nabila Ramadhani Sari; Putri Salsya Nabila; Reza Dwi Cahyo; Rifat Abi Ishaq; Risky Pujianto; Rizky Fadillah Putra Pratama; Rizky Nicolas; Rizky Ziaul Haq; Satrio Agung Wicaksono (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
This community service program is designed to increase the knowledge and awareness of Margahayu Village residents, especially in RW 012, regarding the importance of digital security and cybercrime prevention efforts. With the development of digital technology, the community is increasingly at risk of threats such as personal data theft, online fraud, and phishing practices. Low levels of digital literacy make the community vulnerable to cybercrime. The activities were carried out through field surveys, interactive socialization about various modes of digital fraud, and training on the use of the Village Profile Website. The results of these activities showed an increase in the understanding of the RW 012 community in identifying digital risks, maintaining account privacy, creating secure passwords, and using web-based village information services. Overall, this activity played a role in creating a safer digital environment while strengthening cooperation between universities and the community.